NIR-emitting benzothiazolium cyanines with an enhanced stokes shift for mitochondria imaging in live cells. Issue 18 (19th April 2018) - Abeywickrama, Chathura S.; Baumann, Hannah J.; Alexander, Nicolas; Shriver, Leah P.; Konopka, Michael; Pang, Yi
Abstract : A series of benzothiazolium-based hemicyanines (3a–3f ) have been synthesized. Abstract : A series of benzothiazolium-based hemicyanines (3a–3f ) have been synthesized. Evaluation of their photophysical properties shows that they exhibit improved photophysical characteristics. In comparison with the available commercial MitoTrackers, the new probes revealed an enhanced Stokes shift (Δ λ ∼ 80 nm) and minimized aggregation for increased sensitivity. The synthesized probes are found to exhibit excellent selectivity for mitochondrial staining in an oligodendrocyte cell line. Probes show almost no fluorescence in aqueous environments, while the fluorescence is increased by ∼10-fold in organic solvents, making it possible for mitochondrial imaging without the need for post-staining washing. Since the absorption peaks of probes are close to the laser wavelengths of 561 and 640 nm on a commercial confocal microscope, e.g. 3a exhibits λ abs ∼ 620 nm and λ em ∼ 702 nm, they could be useful probes for mitochondrial tracking in live cells.